Contribuição do Pibid na formação de sujeitos leitores - Ricci, Juliana Tempone [UNESP] (2017)
This paperwork is focused on the sub-project Pibid/Pedagogy on Universidade Estadual Paulista (Rio Claro), which was developed in a municipal school, between 2014 and 2017. The Capes Institutional Program of Scholarships for Teaching Iniciation (Pibid) grants scholarships to Superior Education graduation students and stablishes partnerships with basic public educational institutions. The partnership between university and school in the sub-project Pibid/Pedagogy aimed to constitute readers through collective work between scholarship holders initiating their graduation and teachers, based on practical reading exercises and interdisciplinary projects. Moving towards this objective, this research aims to analyze which were the main Pibid/Pedagogy contributions to constitute readers through practical reading exercises developed by scholarship holders in the sub-project in a partnership with the school's teachers. To do so, the following methods were chosen: a qualitative research based on a documental analysis and a bibliographic research about reading and literature based on: a) readings by the scholarship holders of the sub-project at the meetings; b) Annals of the III Nacional Congress of Teachers Education and the XIII São Paulo's State Congress on Teachers Education (2016) and c) Annals of ANPEd (National Association of Graduate Studies and Research in Education - 2015). The research sets in evidence that the sub-project moved all the school with the reading project in association with the teachers and contributed to extend students interest and passion for reading, supporting their education as critical, criative and autonomous readers